Effect of KH550 - TiO2@ODA - GO on the Anti - Corrosive and Antibacterial Properties of Silicone - Epoxy Resin - ZHANG Jiao, HUANG Feng, LIU Jing, CHEN Yu-shan, YUE Chao-xiong (Cailiao Baohu, 2021)
At present, the reports about the influences of graphene oxide (GO), octadecylamine (ODA) and nano-TiO2 composite on the corrosion resistance and antimicrobial activity of materials have less been studied. In this work, GO was first modified covalently by ODA and then by nano-TiO2 coupling agent KH550 treatment to prepare KH550-TiO2@ODA-GO composite materials. Additionally, XRD, FTIR, FE-SEM methods were used to study the physical property of KH550-TiO2@ODA-GO composites, and the composites were added into silicone modified epoxy resin (SMER) to prepare KH550-TiO2@ODA-GO/SMER composite coating. The anti-corrosion and antibacterial property of the composite coating was studied by scanning Kelvin probe (SKP), electrochemical impedance spectroscopy (EIS), salt spray and antibacterial test. Results showed that the low-frequency resistance value (|Z|0.01 Hz) of KH550-TiO2@ODA-GO/SMER coating immersed in 3.5%(mass fraction) NaCl solution for 28 d was still as high as 2.78×109 Ω·cm2. Besides, the killing rate of KH550-TiO2@ODA-GO/SMER coating to E. coli reached 95%. The high compatibility of KH550-TiO2@ODA-GO with SMER coating not only improved the interfacial bonding force of the coating, but also effectively extended the penetration path of the corrosive medium inside the coating, resulting in the improvement of the anti-peeling performance and thus significantly improving the corrosion resistance of SMER coating. In addition, nano-TiO2 still showed good antibacterial effect in SMER coating after modification and loading on GO surface.